High‐Performance Spin Filters and Spin Field Effect Transistors Based on Bilayer VSe2. Issue 2 (16th December 2020) - Wu, Baochun; Quhe, Ruge; Yang, Jie; Liu, Shiqi; Shi, Junjie; Lu, Jing; Du, Honglin
Abstract: Recently, two‐dimensional (2D) magnetic van der Waals materials have drawn great attention as they are remarkably promising in numerous vital areas, such as data storage and information processing. Theoretically, bilayer (BL) 2H‐VSe2 has been predicted to be an A‐type 2D antiferromagnetic van der Waals crystal (intralayer ferromagnetism and interlayer antiferromagnetism) and to have electrically‐induced half‐metallicity. Herein, by using ab initio quantum transport simulations, BL 2H‐VSe2 spin devices are designed and spin‐resolved transport properties are investigated for the first time. The spin‐filter efficiency (SFE) of the dual‐gated BL 2H‐VSe2 spin filter reaches up to 99%, and the conductance on‐off ratio of this device is up to 10 6 . Also, the conductance on‐off ratio of the quadruple‐gated BL 2H‐VSe2 spin field effect transistor can reach 4 × 10 3 after reversing the spin direction. This work shows the high performance of the BL 2H‐VSe2 in spintronic devices and will motivate further studies of the spin devices based on this kind of material. Abstract : This work assesses the performance of bilayer (BL) 2H‐VSe2 spin devices using ab initio quantum transport simulation. Remarkably, high spin‐filter efficiency and large conductance on‐off ratio are obtained in dual‐gated spin filters and quadruple‐gated spin field‐effect transistors due to electrically‐induced half metallicity. Hence BL 2H‐VSe2 is desirable for application in high‐performance spintronic devices.